(untitled) - T E Gaedel (Upper Saddle River, New Jersey, 1996)
The book discusses steps to improve energy efficiency, minimize residues, choose materials, package new products properly, reduce environmental impacts by products during their useful lives, and design products for recycle. It also explains techniques for evaluating the environmental responsibility of products
Keywords: design industrial - environmental aspects,environmental engineering,product life cycle - environmental aspects